Science Content and Curriculum in the Construction of a Materialist, Historical and Dialectical Worldview - Massi, Luciana [UNESP]; Colturato, Andriel Rodrigo [UNESP]; Teixeira, Lucas André [UNESP] (Investigacoes em Ensino de Ciencias (IENCI), 2022)
The context of emptying scientific content and science curriculum today brought the need to develop this investigation, focusing on the discussions about content and curricula. The objective was to identify and analyze the worldview present in the relations between the scientific concepts of the natural sciences and its conversion into school contents through the articulation with the historical-critical pedagogical theory. Based on historical-critical pedagogy, this objective was accomplished through a systematic literature review of 33 works in the area of Science Education. The analysis showed that the criteria for content selection to the composition of the science curriculum gave centrality to social practice, history, official documents and literature in the area. Although confused with everyday life, social practice is essential for the role of science to be clear in the face of worldviews that are in dispute in society. On the other hand, history, explored from the need to articulate the content in its context of scientific production, showed little relationship with the foundations of the pedagogical process, compromising the teaching objectives in the educational process. Finally, there was a lack of a critical position by researchers when official curricula and literature in the area were sought as a reference for the selection of school science content. These results are important to advance the discussion about school contents with greater articulation and consideration, in the sense of developing a materialist, historical and dialectical worldview in students.
CONTEÚDOS E CURRÍCULOS DE CIÊNCIAS NA CONSTRUÇÃO DE UMA CONCEPÇÃO DE MUNDO MATERIALISTA, HISTÓRICA E DIALÉTICA
Keywords: Curricular Contents; Historical-Critical Pedagogy; Science Education; World Conception